Problems of Ensuring Energy Security in the Focus of Sustainable Development: From Traditional Resources to Alternative Ones - Merkulova, Elena Yu.; Margarita, Sysoeva S.; Svetlana, Samoilova S. (International Journal of Energy Economics and Policy, 2022)
In the presented study, the development of energy-efficient technologies is studied using time series data for the years 1970-2020, which make it possible to ensure the sustainability of Russia’s development. The threats to energy security in the economic, fuel supply, production, transit blocks and the block of reliability of functioning are identified, which give a signal about the need for measures to level them. Based on the synthesis of the theory of sustainability of economic systems, reliability theory, risk theory, system security theory, as well as analysis of modern factors of fuel and energy sector development, strategic guidelines for improving energy security and economically sustainable development of the fuel and energy sector are substantiated. The modern world is characterized by changes in the parameters and directions of the energy economy under the influence of scientific, technical, environmental, economic, organizational and other factors. The process of serious modernization is underway in the global energy sector. The transformation of the global energy sector is carried out within the framework of ensuring sustainable development through the introduction of new energy-saving technologies. Russia’s energy security is based on a rich base of strategic resources and production potential created by the fuel and energy complex, which can ensure the gradual development of the country and its security. However, in recent decades, despite energy independence and independence, the issue of energy security has become more acute for various regions of Russia, which is associated with steadily growing energy needs. The study examines the dynamics of oil and gas production in Russia and the world. The factors of energy security of the Russian economy and the population with generated capacities, which are a barometer of the sustainability of economic development, are identified. The possibilities of transition from traditional energy sources first to REI, and then to inexhaustible natural sources, with the use of new digital technologies for their distribution and consumption in the economy are considered. The specific natural conditions of various regions of Russia are investigated for the possibility of developing alternative energy based on water, wind, solar energy, geothermal energy, wave energy, tides, and biomass energy. The economic, technological, social and environmental effects resulting from the use of energy-efficient technologies are substantiated.